Pengaruh Modal Kerja Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Subsektor Logam Dan Sejenisnya Yang Terdaftar Di Bei Periode 2018-2022 - Sherly Yulita Sari; Edwin Agus Bunairto; Ririn Wahyu Arida (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
The aim of this research is to determine whether there is an influence of working capital and capital structure on company value with profitability as an intervening variable in metal subsector companies and similar companies listed on the IDX for the 2018-2022 period. The sample selection in this study used purposive sampling with a sample of 7 companies with a period of 5 years. The results of this study show that (1) Working capital has a significant effect on profitability, (2) Working capital does not have a significant effect on company value (3) Capital structure has a significant effect on profitability, (4) capital structure has no significant effect on company value and (5) profitability has a significant effect on company value.